Rapid modulation of spoken word recognition by visual primes. (February 2016) - Okano, Kana; Grainger, Jonathan; Holcomb, Phillip J.
Abstract: In a masked cross-modal priming experiment with ERP recordings, spoken Japanese words were primed with words written in one of the two syllabary scripts of Japanese. An early priming effect, peaking at around 200 ms after onset of the spoken word target, was seen in left lateral electrode sites for Katakana primes, and later effects were seen for both Hiragana and Katakana primes on the N400 ERP component. The early effect is thought to reflect the efficiency with which words in Katakana script make contact with sublexical phonological representations involved in spoken language comprehension, due to the particular way this script is used by Japanese readers. This demonstrates fast-acting influences of visual primes on the processing of auditory target words, and suggests that briefly presented visual primes can influence sublexical processing of auditory target words. The later N400 priming effects, on the other hand, most likely reflect cross-modal influences on activity at the level of whole-word phonology and semantics. Highlights: Spoken Japanese words were primed with words written in Hiragana and Katakana. Early priming effect was seen in left lateral regions only in Katakana primes. We report fast-acting influences of visual primes on auditory target words.